(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
We are studying the biology of Ahasverus advena (Waltl). (Coleoptera, Cucujidae, Silvaninae). We can find this species on different food-stuffs, full of moulds that feed this species. During our experiment we have seen that the insect can multiply on different moulds, a few of them can produce micotoxin, belonging to the genus Penicillium and Aspergillus. Therefore is necessary an accurate cereal’s storage that restains the moulds growing and causes a natural control of this pest.